(untitled) (Journal of Global Accounting, 2024)
The main objective of the study is to examine the effect of board diversity on the financial performance of listed consumer goods firms in Nigeria. The specific objective was to determine the effect of nationality diversity (BND), gender diversity of corporate board (BGD) and age diversity of corporate board members (BAD) on cashflow return on investment (CROI) of listed consumer goods firms in Nigeria, with firm size (FSZ) as the control variable. The study adopted ex-post facto research design on a population of twenty-one listed consumer goods firms on the Nigerian exchange group. The sample size of fifteen firms used in the study was determined through purposive sampling. Secondary data were sourced from the firms’ annual reports over a period of ten (10) years, covering the years 2013 to 2022. Panel-corrected standard errors (PCSE) regression was applied in testing the hypotheses, which revealed that: Nationality diversity has a negative but insignificant effect on cashflow return on investment of listed consumer goods firms in Nigeria (p-value = .359); Gender diversity has a positive but non-significant effect on the cashflow return on investment of listed consumer goods firms in Nigeria (p-value = 0.080); Age diversity has a positive and significant effect on the cashflow return on investment of listed consumer goods firms in Nigeria (p-value = 0.007). In conclusion, the negative impact of nationality diversity on cashflow return on investment shows the need for organizations to carefully manage the challenges associated with diverse national backgrounds, emphasizing effective communication and cultural alignment. It is recommended that organizations should carefully evaluate and manage the composition of their leadership teams with regard to nationality by fostering inclusive leadership practices and providing cross-cultural training to mitigate potential challenges associated with nationality diversity and enhance overall financial performance.